THE EFFECT OF HYPNOBIRTHING ON ANXIETY LEVELS IN THIRD TRIMESTER PREGNANT WOMEN - Shania Juniarti; Nova Ayu Maulita (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Anxiety in third trimester pregnant women is a common condition and can impact the labor process and the well-being of the mother and fetus. One non-pharmacological method that can be used to reduce anxiety levels is hypnobirthing. This study aims to determine the effect of hypnobirthing on the anxiety levels of third trimester pregnant women at TPMB Ziandta in 2025. This type of research is quantitative with a pre-experimental design using a one-group pretest–posttest approach. The population in this study were all third trimester pregnant women who underwent pregnancy check-ups at TPMB Ziandta, with a sample of 31 respondents taken using an accidental sampling technique. Data collection was carried out using an anxiety level questionnaire. Data were analyzed using a T-Test statistical test. The results showed that there was an effect of hypnobirthing on the anxiety levels of third trimester pregnant women with a p value = 0.000 (<0.05). The conclusion of this study is that hypnobirthing has a significant effect on reducing the anxiety levels of pregnant women in the third trimester at TPMB Ziandta in 2025. It is hoped that hypnobirthing can be implemented as a non-pharmacological intervention in antenatal care to help pregnant women manage anxiety before childbirth.